2013
DOI: 10.1371/journal.pone.0071065
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Hypothalamus-Pituitary-Adrenal/Thyroid Axes and Gonadotropin-Releasing Hormone in the Patients with Primary Insomnia: A Clinical Research

Abstract: The hypothalamus-pituitary-target gland axis is thought to be linked with insomnia, yet there has been a lack of further systematic studies to prove this. This study included 30 patients with primary insomnia (PI), 30 patients with depression-comorbid insomnia (DCI), and 30 healthy controls for exploring the alterations in the hypothalamus-pituitary-adrenal/thyroid axes’ hormones and gonadotropin-releasing hormone (GnRH). The Pittsburgh Sleep Quality Index was used to evaluate sleep quality in all subjects. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…However, it is possible that alterations in neuroendocrine hormones, including hormones of the HPA axis, the HPT axes, and GnRH, have detrimental effects on memory formation, synaptic plasticity, and neurogenesis (Fuite, Vernon, & Broderick, ; Kamath, Yarbrough, Prange, & Winokur, ; Morale et al, ; Rohleder, Schommer, Hellhammer, Engel, & Kirschbaum, ). Both our previous study (Xia et al, ) and the present study showed that patients with insomnia had elevated morning serum levels of CRH, cortisol, TRH, total triiodothyronine, total thyroxine, and GnRH (Figure and Table ). Therefore, it is possible these alterations in hormone levels exert a negative effect on multiple aspects of the memory system in patients with insomnia.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, it is possible that alterations in neuroendocrine hormones, including hormones of the HPA axis, the HPT axes, and GnRH, have detrimental effects on memory formation, synaptic plasticity, and neurogenesis (Fuite, Vernon, & Broderick, ; Kamath, Yarbrough, Prange, & Winokur, ; Morale et al, ; Rohleder, Schommer, Hellhammer, Engel, & Kirschbaum, ). Both our previous study (Xia et al, ) and the present study showed that patients with insomnia had elevated morning serum levels of CRH, cortisol, TRH, total triiodothyronine, total thyroxine, and GnRH (Figure and Table ). Therefore, it is possible these alterations in hormone levels exert a negative effect on multiple aspects of the memory system in patients with insomnia.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, hormones of the hypothalamic-pituitarythyroid (HPT) axis and hypothalamic-pituitary-gonadal axis influence memory function (Galea et al, 2013;Gan & Pearce, 2012;Grigorova & Sherwin, 2012). Our previous study found neuroendocrine alterations in patients with chronic primary insomnia (Xia, Chen, Li, Jiang, & Shen, 2013); however, the role of neuroendocrine alterations in the memory impairments observed in patients with chronic insomnia disorder (CID) is unclear.…”
mentioning
confidence: 99%
“…Our result that PSG‐determined TST was predicted by somatic presleep arousal supports the hyperarousal model of insomnia (Riemann et al ., ). Research suggests that a persistent increase of physiological arousal in patients with PI is associated with reduced activity of the parasympathetic nervous system (Farina et al ., ; Spiegelhalder et al ., ; Yang and Lo, ) and increased activity of the hypothalamic–pituitary–adrenal axis (HPA axis) (Xia et al ., ; Zhang et al ., ) as shown, for example, by increased cortisol levels. Some evidence also suggests that increased cortisol levels were correlated with PSG‐determined sleep disturbance (Vgontzas et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies of patients with primary insomnia (PI) and good sleeper controls (GS) have identified peripheral nervous system (PNS) markers of hyperarousal that seem to support this intuitive explanation, linking insomnia to heightened body temperature [2], greater 24-h metabolic rate [3], and more rapid heart rate and elevated low-frequency power in heart rate, a marker of sympatho-vagal balance, during sleep [4]. Heightened cortisol levels, particularly in the pre- and early-sleep periods, have also been linked to insomnia, a finding interpreted by some as evidence of central nervous system (CNS) hyperarousal in insomnia [5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%